Concept of Humus - Tan, Kim H. (Humic Matter in Soil and the Environment, 2014)
As discussed in the preceding chapter, soil organic matter is a term frequently used to indicate the dead organic fraction only, and the live fraction, although of equal importance, is usually ignored. This dead organic fraction was divided in the previous chapter into two groups: a group of organic matter at various degrees of decomposition, related to litter, and another group composed of completely decomposed materials, which was identified as humus. The first group mentioned above, containing most of the undecomposed material, has been discussed in the preceding chapter. The present chapter is intended to continue by now examining the concepts and issues of the second group of organic matter, known as humus. The term humus (Latin for soil, earth, ground, or vegetation) is a name that seems to be accepted by many scientists from the early days until late in the twentieth century for organic residues, composed of brown to black amorphous materials with no traces of any cellular structures of the original plant and animal materials. Merriam-Webster’s Dictionary also defines humus as a “brown or black to complex variable material resulting from partial decomposition of plant and animal matter and forming the organic portion of soils” (Merriam-Webster, 1973). The nature of this highly complex system, called humus, is still confusing until today. Most people in the past seem to associate it with the NaOH-extractable fraction of soil organic matter (Russell and Russell, 1950; Whitehead and Tinsley, 1963). However, this alkali-soluble part is, by definition, the soil humic substances, and the example of Waksman’s ligno-protein compound presented as evidence of humus by Whiteheadand Tinsley (1963) is only adding to the confusion because this is the classic polymer concept of humic acid. Considering humus as equivalent to humic matter was very common in those years, and even Flaig (1975) and more recently Haider (1994), prominent authorities on the subject, use the terms humus and humic matter interchangeably. Kumada (1987) adds to the confusion by using in his book the terms SOM (soil organic matter) and humus synonymously, whereas Schnitzer’s (2000) statement that he, personally as a SOM scientist, prefers the use of the term SOM for humic substances, makes the issue more confusing. Apparently, the old ideas seem to convey the message that humus is, in essence, nothing more than humic matter, which seems to boil over into the modern ideas of the new millennium. Such a concept is subject to many arguments since it ignores the materials extracted along and that are discarded during purification of the humic substances. Then, there are substances that are not extracted and remain in the residue, whose origin came from the sample defined as humus. The definition agreed on by most scientists also spells out that humus refers to all organic plant materials that have been decomposed to an “unrecognizable” amorphous mass. Page (1930) suggests dropping the term humus and replacing it with the names nonhumic and humic matter. Page groups fulvic acid and colorless decomposition products of organic matter under the name nonhumic matter. The dark or black materials are grouped as the humic fraction. However, Waksman (1938) proposes just the opposite in his famous book-to drop the names of nonhumified and humified fractions altogether and just use the name humus for soil organic matter. Failure to find a satisfactory agreement in the following years has resulted in a lot of confusion on the nature of humus. The present author suggests retaining the name humus and dividing it into nonhumified and humified fractions (Tan, 1986). Whether this idea caught on is perhaps conjecture, because since then similar definitions have surfaced in the more modern literature recognizing humus to be composed of a nonhumic and a humic fraction (Brady and Weil, 2008; Stevenson, 1994). Wershaw (2004) calls this “mixture”—known as humus-NOM (natural organic matter), apparently following Stevenson’s (1994) idea, which considers soil organic matter identical to humus. In his book, Stevenson lists the definition of soil organic matter as “same as humus” (Stevenson, 1994; Humus Chemistry, see table 2.3, p. 33). However, Stevenson’s idea cannot be considered original or new because it is an adaptation, if not a quotation, of an older concept developed by Waksman (1938). As indicated earlier, it was in fact Waksman who originally proposed using the name humus only for referring to soil organic matter.